New Ruthenium (II)Palladium (II) and Platinum (II) Complexes of Heterocyclic Organochalcogenide Ligands: Synthesis, Characterization, and Evaluation of Anticancer Activity Against Breast Cancer Cells - Hayat Hamza Abbas; Mohammed J.B. Al-assadic; Majeed Y. Al-Luaibib (Indonesian Journal of Chemical Science, 2023)
This work aimed to synthesize, characterize of Ruthenium (II)Palladium (II) and Platinum (II) Complexes and to test the cytotoxic activity, against breast adenocarcinoma cell line (MCF-7) through conducting MTT assay and AO/EB dual staining-technique. Given our efforts ton toward the synthesis of coordination compounds with potential chemotherapeutic properties, we report In this manuscript, the synthesis, of seven new Ru(II), Pd(II), and, Pt(II) complexes with mono- and bidentate organo-chalcogenide ligands formulated [M2-μ-2Cl(L)4 ]Cl2 and [M(L)2 ]Cl2 of M=Ru(II) and Pd(II), Pt(II) respectively [where L= 4-phenylthiomorpholine-3,5-dione[I], 4-phenylselenomorpholine-3,5-dione[II] and O-chlorophenylselenomorpholine-3,5-dione[III]]ligands, which characterized by elemental analysis C.H.N, FTIR, UV-VIS, MSD-mass spectrometry, 1H NMR, 13C NMR, molar conductivity measurements and magnetic susceptibility. The preliminary cytotoxic activity of these compounds was evaluated against human breast carcinoma, MCF-7 and normal, breast cells, HBL-100 by a colorimetric viability assay based on enzymatic reduction of the MTT molecule to formazan when it is exposed to viable cells. To elucidate the apoptotic activity of the prepared compounds, the acridine orange/ethidium bromide (AO/EB) staining technique was conducted. The DNA binding activity of one of these ligands and it, s corresponding Ru complex was confirmed by electronic spectroscopy studies. It was found at ligand(II) has stronger DBA than it, s corresponding Ruthenium complex(V).